Frequency of Adjunctive Treatments Requiring Referrals among Patients at Prosthodontics Department in Pakistan - Qureshi, Ali Waqar; Sunny, Adnan; Waleed Babar, Sardar; Ahsan, Areesha; Hasan Idris, Shujaat; Khan, Natasha (Pakistan Armed Forces Medical Journal, 2024)
Objective: To report the frequency and types of adjunctive treatments requiring referral for patients in the Prosthodontics Department in Pakistan.Study Design: Cross-sectional study.Place and duration of study: The study was conducted in Prosthodontics Department, Peshawar Dental College, Peshawar from April 2020 to October 2020.Methodology: The study involved 218 patients reporting to the outpatient department of the Prosthodontics department, both genders, with no prior prosthodontic experience. Following the establishment of the diagnosis, and treatment plan via history taking and examination, a decision for referral for adjunctive treatment required was made and noted in the patients’ record file, and this data was collected in a pre-structured proforma.Results: In total, 218 patients who attended the Department of Prosthodontics were evaluated. The referrals made to the Departments of Operative Dentistry and Endodontics were of 97(44.49%) patients, Oral and maxillofacial Surgery (OMFS) were 61(27.98%) patients, followed by Periodontology were 58(26.60%) patients, while Orthodontics for only 2(0.92%) patients. A statistically significant association of these referrals was observed with the gender as well as the oral hygiene status of the patients with a p-value of 0.001 and 0.021. However, the association of these referrals with the socioeconomic status of the patients was statistically insignificant with a p- value of 0.604.Conclusion: Referrals needed to the Operative/Endodontics Department were more followed by Oral And Maxillofacial and Periodontics Department. The least referrals were those of Orthodontics.